PERMASALAHAN PUTUS SEKOLAH PENDIDIKAN DASAR - Rizki, Rizki Ananda; sary, SYARY KURNIA PUTRI; Nia, Nia ayu lestari; Dinda, Dinda Harini; Ilham, M.Ilham Adriansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Dropping out of primary education in Indonesia is a serious issue that impacts the quality of human resources and national development. Although the government has implemented a nine-year compulsory education program, data shows that thousands of children still do not complete basic education. The causes are diverse, including family economic conditions, limited access to education, cultural factors, and lack of support from the surrounding environment. This article aims to analyze the factors contributing to dropout rates in primary education in Indonesia by reviewing relevant news and academic journals. The method used is a literature study based on secondary data from official government reports, recent news articles, and scholarly publications. The analysis reveals that economic factors, such as poverty and the need for children to work, are the main causes. In addition, geographical factors such as remote locations, and socio-cultural issues like early marriage and lack of awareness about the importance of education, also contribute. Efforts to address the issue include alternative education programs, volunteer teaching initiatives, and counseling support by educators. However, challenges remain significant, especially in underdeveloped, frontier, and outermost (3T) areas. A holistic approach involving all stakeholders is needed to effectively address this problem.